RĂZBOIUL DIRECTORILOR” MUZEULUI NAȚIONAL DE ISTORIE NATURALĂ DIN CHIȘINĂU LA ÎNCEPUTUL ANILOR’30 - Rotaru, Liliana; Ciobanu, Tudor; Ponomarev, Alexandr (Lexon-Prim, 2022)
Nicolae Florov (Florea), doctor of sciences from the University of Iași (1925), agrogeologist and soil science specialist of European stature, museographer, university professor (1931) and man of culture was born on December 19, 1876, in the village of Cornești, county Balti in the family of priest Pavel Florov. After a directorship of almost 10 years at the National Museum of Natural History in Chisinau, the Ministry of Public Instruction of Romania decides to replace Nicolae Florov with Teodor Porucic in the summer of 1931, a replacement, which produced an avalanche of dissatisfaction from the new director, materialized in notes, information and notifications addressed to the Chisinau police. The authors analyzed these notifications, contained in the files of the Iași Police Investigations, kept in the National Archives of Romania and the National Archives of the Republic of Moldova, and tried to unravel the causes of Teodor Porucic’s institutionalized “upsets” and the role of Nicolae Florov in their production.
The “war of the directors” of the National Museum of Natural History in Chisinau in the early 1930s
Keywords: Frolov, Nicolae